Biophysics: tools and techniques - Leake, Mark C. (CRC Press, 2016)
"This book concerns one, simple question: What is life? If only the answer were as simple! In this book you will find a comprehensive discussion of the experimental and theoretical tools and techniques of biophysics which can be used to help us address that most innocuous of questions"--